Pertanggungjawaban Perdata Tenaga Kesehatan Atas Prosedur Estetika Dihubungkan dengan Informed Consent Berdasarkan Peraturan Perundang-Undangan - Wulandari, Davina Cantika; S. Sewu, Pan. Lindawaty (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The development of aesthetic medical procedures in Indonesia has grown rapidly in line with the increasing public awareness of appearance and quality of life. Aesthetic services, which are elective in nature, often raise legal disputes when the results of medical actions do not meet patients’ expectations or cause harm. In the context of national health law, informed consent is a mandatory requirement that must be fulfilled prior to any medical intervention. This obligation is stipulated in Article 329 of Law Number 17 of 2023 concerning Health, which emphasizes that every medical action must obtain consent that is given consciously, voluntarily, and based on complete information. This requirement reflects both the protection of patients’ rights and the professional responsibility boundaries of health workers in performing medical practices.This research employs a normative juridical method using statutory, conceptual, and case approaches to analyze the forms of civil liability of health professionals in aesthetic procedures when the principle of informed consent is violated. The study finds that failure to fulfill the requirements of informed consent may result in civil liability for health professionals, either in the form of breach of contract as regulated in Article 1239 of the Indonesian Civil Code, or tort liability under Article 1365 of the Indonesian Civil Code. Furthermore, the Health Law of 2023 reinforces the importance of professional standards, medical ethics, and legal protection mechanisms for both patients and health professionals as part of an integrated health service system. Therefore, informed consent holds a strategic position as a legal instrument that not only safeguards patients’ rights but also strengthens the professional accountability of health practitioners in carrying out aesthetic procedures that are safe, ethical, and legally compliant.